Composite resin shear bond strength on bleached dentin increased by 35% sodium ascorbate application - Tunjung Nugraheni; N Nuryono; Siti Sunarintyas; Ema Mulyawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: Restoration of the teeth immediately after bleaching with 35% hydrogen peroxide (H2O2) is contraindicated due to the remnant of free radicals that will stay inside enamel and dentin for 1-3 weeks and reduce the adhesion of composite resin. Sodium ascorbate is an antioxidant substance known to bind free radical residues, thereby shortening the delay in restoration. Purpose: The purpose of this study was to examine the resin bond strength of bleached dentin influenced by the application of 35% sodium ascorbate. Methods: Nine premolars were divided into their crown and root sections, with the crown subsequently being cut into four equal parts to obtain 36 samples. These were then divided into four groups, each containing nine samples. Group A (control): samples were bleached using35% hydrogen peroxide, immersed in an artificial saliva, stored in an incubator at 37°C for seven days and then filled with a composite resin. Group B:samples were also bleached by means of 35% H2O2 followed by one application of 0.025 ml 35% sodium ascorbate for 5 minutes and restored with composite resin. Group C: samples were bleached with 35% H2O2, followed by two applications of 0.025 ml 35% sodium ascorbate for 5 minutes, and restored with a composite resin. Group D: dentin was bleached with 35% H2O2 followed by three applications of 0.025 ml sodium ascorbate 35% for 5 minutes and restored with a composite resin. The shear bond strength of the composite resin was measured by a universal testing instrument (Zwick, USA). Data was analyzed by means of one-way Anova and LSD. Results: The highest mean shear bond strength of composite resin was in group C, while the lowest was in group B. The result of one-way Anova indicated a difference in the shear bond strength of composite resin in the four treatment groups (p < 0.05). An LSD test showed there to be a difference in shear bond strength of composite resin between group A and groups C and D or between group B and groups C and D. There was no difference in shear bond strength of composite resin between group A and group B or between group C and group D. Conclusion: Application frequency of 35% sodium ascorbate affect on shear bond strength of composite resin restoration in bleached dentin by 35% H2O2.